Macroeconomic models and planning in the context of an uncertain future: the French experience - Paul Dubois (CEPAL Review, 1987)
Enorm ous structural adjustm ents are needed in order to emerge from the crisis, and this makes it more vital than ever to think in the medium and long terms. The failure of the policies of the past has largely been due to their negligence vis-a-vis the future: negligence concerning income form ation unfavourable to investm ent and the creation of employment and price stability; negligence concerning deficits resulting in growing indebtedness; negligence concerning the lack of a systematic training and research effort; and negligence concerning the absence of institutions capable of ensuring the maintenance of the kind of intern ational economic order needed in a world in which the interdependence among countries has increased significantly.